Gene effects for different traits of spike morphology in wheat (Triticum aestivum) - KUMAR, PAWAN; YADAVA, RAMESH KUMAR; GOLLEN, BABITA; SHEORAN, O P (The Indian Journal of Agricultural Sciences, 2026)
The present investigation was carried out to analyse gene effects for spike morphology under two growing seasons. Six wheat (Triticum aestivum L.) genotypes were selected to generate the experimental material comprised six parental and segregating generation (P1, P2, F1, F2, BC1 and BC2 ) of each of the following six crosses: HS 27 × PBW 502(C-I); HS 67 × PBW 502 (C-II); HJP 81 × PBW 502 (C-III) and HG 2 × HD 2009M (C-IV). The chi square was used to estimate the adequacy of the three parameter model, most of the characters showed the adequacy of the six parameter models indicating the presence of epistasis. Joint scaling tests revealed the presence of epistasis. Some characters like spike length in C-I (S2), C-II (SII); number of spikelets/spike in C-II (S1) and number of fertile spikelets/spike indicates the adequacy of three parameter model, i e no digenic interaction there. The epistatic gene effects were predominant over additive and dominance effects under both growing seasons. Duplicate gene interaction was observed in most of the characters which is difficult to exploit in breeding programs.